Africa Fertilizer and Soil Health Action Plan: Outcome 2 - African Union Development Agency- NEPAD (2024)
This poster presents Outcome 2 - ‘Improved Access and Affordability of Organic and Mineral Fertilizers’ of the Africa Fertilizer and Soil Health (AFSH) Action Plan. It gives the AFSH Action Plan’s Vision, Expected Impact, Strategy and the contributing Outcome 2 with associated Outputs (2.1 and 2.2) and Action areas.